2000
DOI: 10.1086/308793
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Element Evolution and Cosmic‐Ray Energetics

Abstract: Using cosmic-ray energetics as a discriminator, we investigate the viability of evolutionary models for the light elements, Li, Be and B (LiBeB). We employ a Monte Carlo code which incorporates hitherto ignored effects, the delayed mixing into the ISM both of the synthesized Fe, due to its incorporation into high velocity dust grains, and of the cosmic-ray produced LiBeB, due to the transport of the cosmic rays. We use supernova O and Fe ejecta based on calculations and observations, and we normalize the LiBeB… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
133
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(145 citation statements)
references
References 71 publications
9
133
2
Order By: Relevance
“…However, the trend of [S/Fe] versus [Fe/H] in the early Galaxy is still debated: Israelian & Rebolo (2001) and Takada-Hidai et al (2002) found [S/Fe] to rise with decreasing [Fe/H], while Ryde & Lambert (2004) and Nissen et al (2004Nissen et al ( , 2007 found [S/Fe] to remain flat. Finally, Caffau et al (2005Caffau et al ( , 2010a, combining their own data with a large sample from the literature covering the multiplets 1, 3, 6, and 8 of S I (see Table 1), suggest a bimodal distribution of [S/Fe] Nakamura et al 2001), or even that they may be responsible for a delayed deposition of the supernova-synthesized products into the interstellar medium (Ramaty et al 2000).…”
Section: Introductionmentioning
confidence: 93%
“…However, the trend of [S/Fe] versus [Fe/H] in the early Galaxy is still debated: Israelian & Rebolo (2001) and Takada-Hidai et al (2002) found [S/Fe] to rise with decreasing [Fe/H], while Ryde & Lambert (2004) and Nissen et al (2004Nissen et al ( , 2007 found [S/Fe] to remain flat. Finally, Caffau et al (2005Caffau et al ( , 2010a, combining their own data with a large sample from the literature covering the multiplets 1, 3, 6, and 8 of S I (see Table 1), suggest a bimodal distribution of [S/Fe] Nakamura et al 2001), or even that they may be responsible for a delayed deposition of the supernova-synthesized products into the interstellar medium (Ramaty et al 2000).…”
Section: Introductionmentioning
confidence: 93%
“…The form of the injection spectrum is motivated by theories of collisionless shock acceleration (e.g. Ellison & Ramaty 1985) and we adopt here the frequently used Fields et al 1994Fields et al , 2001Ramaty et al 1997Ramaty et al , 2000 momentum spectrum of the form…”
Section: Composition Of Gcrmentioning
confidence: 99%
“…To summarize, early studies by Israelian & Rebolo (2001) and Takada-Hidai et al (2002) found that the relative sulphur abundance continuously increases in the metallicity range from solar to at least [Fe/H] −2.5, implying a different chemical evolution history from that of other α-elements, which display a (nearly) metallicity-independent enrichment with respect to iron in stars of low ([Fe/H] −1) A&A 559, A115 (2013) metallicity (Cayrel et al 2004;Jonsell et al 2005) 1 . A high rate of sulphur-rich hypernovae (e.g., Nakamura et al 2001) and a time-delayed deposition of iron into the interstellar medium (Ramaty et al 2000) have been proposed as possible explanations for these unexpected results. On the other hand, a number of studies (e.g, Ryde & Lambert 2004;Korn & Ryde 2005;Nissen et al 2007;Spite et al 2011) have found little to no evidence of high ([S/Fe] 0.6) sulphur abundances at any metallicity and instead argued that sulphur is a fairly typical α-element and forms a plateau of [S/Fe] ∼ 0.3 below [Fe/H] ∼ −1, which points to an origin in Type II supernovae (e.g., Kobayashi et al 2006).…”
Section: Introductionmentioning
confidence: 99%